2013
DOI: 10.1080/02786826.2013.809401
|View full text |Cite
|
Sign up to set email alerts
|

A Generalized Sky-LOSA Method to Quantify Soot/Black Carbon Emission Rates in Atmospheric Plumes of Gas Flares

Abstract: A new generalized theory governing sky-LOSA measurements (line-of-sight attenuation measurements of sky-light) of soot mass flux in atmospheric plumes has been developed which enables accurate measurements in the presence of in-scattered light from the sky and sun. The new approach is quantitatively tested using field measurement data collected for a gas flare at a turbocompressor station in Mexico. Although the soot plume of the tested flare was on the threshold of visible to the naked eye, the sensitivity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 37 publications
1
56
0
Order By: Relevance
“…As pointed out in various studies 13,14,17,22 , the gas flaring BC emission factors could vary significantly among different oil and gas fields. McEwen and Johnson 10 established the first empirical relationship between BC emission factors and volumetric fuel heating values for a range of conditions by imitating flares at the laboratory scale.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…As pointed out in various studies 13,14,17,22 , the gas flaring BC emission factors could vary significantly among different oil and gas fields. McEwen and Johnson 10 established the first empirical relationship between BC emission factors and volumetric fuel heating values for a range of conditions by imitating flares at the laboratory scale.…”
Section: Methodsmentioning
confidence: 95%
“…By using an advanced optical technique sky-LOSA (Line-Of-Sight Attenuation), the emission factor measured in the gas flaring field of Uzbekistan 13 and Mexico 14 was determined to be 2±0.66 and 0.067±0.02 g s −1 , respectively. Nine flight measurements in March 2014 over the Bakken oil-producing region of North Dakota estimated a flaring BC emission factor of 0.13±0.36 g m −3 and an upper bound value of 0.28 g m −3 based on black carbon mass (SP2: Single Particle Soot Photometer) and absorption measurements (PSAP: Particle Soot Absorption Photometer), respectively 15 .…”
Section: Background and Summarymentioning
confidence: 99%
“…Since the gas flaring volume is usually reported in the unit of bcm (billion cubic meters), it is difficult to use the mass emission rate for the estimation of BC emission. In addition, the two studies above showed a factor of over 30 times difference for the soot mass emission rates, which was attributed to the different characteristics of flares in different regions [ Johnson et al , ]. This suggests that a representative emission factor is needed for a best estimation of the gas flaring BC emission of Russia in this study, as well as for other regions with regard to building a global gas flaring emission inventory.…”
Section: Methodsmentioning
confidence: 99%
“…To the authors' knowledge, only two studies have reported spatially-resolved measurements of f v within buoyant non-premixed turbulent flames (Coppalle & Joyeux, 1994;Xin & Gore, 2005). Xin & Gore (2005) Johnson et al, 2011;Johnson et al, 2013). A summary of the recent literature reporting soot measurements in both momentum-and buoyancydominated turbulent non-premixed flames is presented in Yang and Köylü, 2005a Soot volume fraction, primary particle size, aggregate size 0D C2H4 Turbulent jet non-premixed Experimental  Time-averaged measurements of fv, dp and Rg using local extinction and ELS to allow assessment of numerical models.…”
Section: Turbulent Non-premixed Flamesmentioning
confidence: 99%
“…Gas flaring in the petroleum industry is a potentially significant source of global soot emissions given that satellite data indicate global flared volumes exceed 135 billion m 3 annually (Elvidge et al, 2009). Accurate estimation of soot emissions to meet reporting regulations and support informed policy decisions is difficult due to the limited literature for buoyancy-dominated turbulent non-premixed flames, the questionable relevance of existing emission factor models (see McEwen & Johnson 2012), and the challenges of in-situ field measurements Johnson et al, 2013). Most previous studies reporting spatially-resolved measurements of soot in non-premixed turbulent flames have focused on momentum-dominated flames (e.g.…”
Section: Introductionmentioning
confidence: 99%